Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

y = -5x
-2x − y = 0
help


Sagot :

so use subsitution
y=-5x
-2x-y=0
so subsitute -5x for y since the first equation tells us that y=-5x
-2x-(-5x)=0
-2x+5x=0
3x=0
x=0
subsiutte
y=-5x
y=-5(0)
y=0

x=0
y=0
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.